IMPLIKASI PERMAINAN TEBAK WAJAH TERHADAP PERKEMBANGAN BAHASA EKSPRESIF ANAK USIA DINI - Veryawan veryawan Juliati juliati Rabitah Hanum Hasibuan (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
Language skills have a central role in the intellectual, social, and emotional development of children, and are a supporter of success in learning all fields of study in higher education. Language skills are important in communication, especially receptive language skills and expressive language skills. Speaking is included in the development of expressive language. Face guessing game is an option in developing expressive language development in early childhood. Guess the face is a game that trains and recognizes various kinds of facial expressions and then mentions the picture of those facial expressions. This research was conducted at KB As Salam which is located at Jl. Education No. 142 Ex. Mabar Downstream District. Medan Deli, Medan City. This study consisted of 2 cycles, starting from January 13 to January 31, 2020. The subjects of this study were KB As Salam students in group B II, totaling 15 people consisting of 9 women and 6 men with a recreational theme. The research used is classroom action research carried out by teachers as well as researchers in their class or together with other people (collaboration) by designing, implementing and reflecting collaborative and participatory actions that aim to improve or improve the quality of the learning process in the classroom through a certain action (treatment) in a cycle. The results showed that the level of success in playing guessing games on the development of expressive language in early childhood showed very good development and had reached the level of development in accordance with expectations, namely 80%. Thus, through the activities of guessing faces on the development of expressive language in early childhood.